Legal Regulation of AI and Morality: The Artificial Intelligence Act in the Context of Natural Law and Legal Positivism - Grumulaitis, Artūras (Teisė, 2025)
This paper analyses the relationship between the proposed EU regulation on Artificial Intelligence (AI) and morality, looking from the perspective of two legal paradigms: natural law and legal positivism. The categories of ‘ethics’ and ‘morality’ are being increasingly discussed in the context of advanced technologies, raising the question of whether everything that AI presents is acceptable and tolerable. Based on the essential characteristics of natural law and legal positivism paradigms, legal doctrine, and the newest AI regulation initiatives in the EU, the paper seeks to clarify how the intrinsic morality of natural law influences the legal regulation on AI, and how deep this morality is reflected in the AI Act.
Keywords: artificial intelligence; legal positivism; natural law; ethics; moral; legal paradigm